Acute Neuro-Behçet's Disease - Takeuchi, Hideyuki (Brain and nerve = Shinkei kenkyū no shinpo, 2021)
Neuro-Behçet's disease accounts for 10-20% cases of Behçet's disease, and patients manifest neurological symptoms due to parenchymal inflammation in the central nervous system. Neuro-Behçet's disease is classified into two types (acute and chronic progressive) based on clinical symptoms and therapeutic responsiveness. This review aimed to summarize the acute type of neuro-Behçet's disease according to the guidelines of the Japanese Behçet's Disease Research Committee.